The use of alcohol as a social mediator among university students - Soares, Wellington Danilo; Paz, Carolina Júnia Reis; Fagundes, Ludmila Cotrim; Freitas, Daniel Antunes; Jones, Kimberly Marie; Barbosa, Henrique Andrade (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2018)
INTRODUCTION: alcohol consumption is higher among college students and generates negative consequences. The habits adopted during this period of life are decisive because, for the most part, they will be maintained throughout life. OBJECTIVE: to evaluate the scientific production about the use of alcohol as social mediator among college students. METHOD: integrative review made in the Latin American and Caribbean Health Sciences Literature (LILACS), PUBMED and Scientific Eletronic Library Online (SciELO). Two combinations of the five descriptors were used, namely: Alcohol consumption; AND Students; AND Higher Education; AND Socialization; AND Alcohol. RESULTS: a total of 665 articles were found in the initial search; after careful analysis and application of the selection criteria, 21 articles were used. As for the design, there were 14 qualitative studies, 5 randomized controlled trials, 1 non-randomized trial and 1 cohort study, prevailed. CONCLUSION: alcoholism among college students is a problem in education and health and requires effective action to control its short- and long-term consequences.